ANALISIS MINAT BELAJAR SISWA TERHADAP MATA PELAJARAN FISIKA DI SMA - Miranda; Sutrisnawati Mehora (STKIP Subang, 2026)
This study aims to analyze high school students' interest in physics. The background of the study stems from the fact that physics is often perceived as a difficult, boring, and intimidating subject by some students, resulting in low motivation and participation in learning activities. The study used a qualitative descriptive method using literature review techniques and distributed questionnaires to students. The results showed that although most students had similar tendencies in choosing certain answers, there were still variations in views reflecting differences in experience and background. The data obtained showed that interest in physics is not uniform across all students, but is influenced by both internal factors (such as motivation, emotions, and intellectual ability) and external factors (such as family support, the environment, and learning methods). Therefore, increasing student interest in physics requires learning strategies that are more interactive, engaging, and relevant to everyday life.